PENERAPAN SISTEM TANGGUNG RENTENG PADA KOPERASI WANITA SERBA USAHA â€œSETIA BUDI WANITAâ€ MALANG - Rahayu, Yayuk Sri (IQTISHODUNA, 2009)
This research aimed to describe the implementation of tanggung renteng system and the role of women at Kopwan Setia Budi Wanita Malang. Tanggung renteng system is a sharing responsibility and implementation of collectivity concept on everyone at cooperation. Descriptive analysis was used to get the answer of the purpose. The results shows, first, the implementation of tanggung renteng system consists of decision making process (acceptance of new member), finansial (loan), risk, and the future of cooperation. The increase in member, asset, omzet, and profit shows the success of implementation of this system. Second, women take a part on cooperation development sinc they can increase family economic and natinal economic in general.